Strategic Management of Human Capital in Education: Improving Instructional Practice and Student Learning in Schools - Odden, Allan R. (Routledge, 2011)
Strategic Management of Human Capital in Education offers a comprehensive and strategic approach to address what has become labeled as "talent and human capital." Grounded in extensive research and examples of leading edge districts, this book shows how the entire human resource system in schools—from recruitment, to selection/placement, induction, professional development, performance management and evaluation, compensation, and career progression—can be reformed and restructured to boost teacher and principal effectiveness in ways that dramatically improve instructional practice and student learning. Strategic Management of Human Capital in Education guides educators towards putting more effective teachers, teacher leaders, and principals in the country’s schools—especially in poverty-impacted urban and rural communities—equipping those teacher and principals with instructional and leadership expertise, and rewarding and retaining those who are successful in attaining these objectives. Drawing from cases, experiences, and deliberations from a national task force, this book outlines a comprehensive framework for how to transform current human resource management practices into authentic, strategic talent management systems in order to improve student achievement. 1. Strategic Management of Human Capital in Education: A Framework 2. A Powerful Education Improvement Strategy 3. Staffing and Recruiting Top Talent 4. Performance Management in Education 5. Measuring Teacher Performance for Strategic Human Capital Management, Anthony Milanowski 6. Induction and Professional Development 7. New Policies for Licensure, Tenure, Evaluation and Dismissal 8. The Compensation Side of Strategic Talent Management 9. Strategic Talent Management for Principals, Steven Kimball 10. Organizing to Implement Strategic Talent Management in Education, Allan Odden, Anthony Milanowski, and Steven Kimball 11. The State Role in Strategic Management of Education Talent 12. The Policy and Political Environment for Change, James A. Kelly "Rooted in improving student achievement, the book shows how strategy for developing people overlays with strategy for developing rigorous college ready curricula." —Teachers College Record "This important new book clearly and comprehensively addresses the new work in school reform that is changing the face of human resources in school systems." -- From the Foreword by Carl A. Cohn, Professor and Co-Director, Urban Leadership Program, Claremont Graduate University "All the reorganization and restructuring in the world cannot compensate for poorly selected and developed personnel. Allan R. Odden provides future education leaders a comprehensive foundation for ensuring that school systems recruit, select, retain, and develop educators capable of meeting the challenges of high-stakes schooling." -- Daniel L. Duke, Professor of Educational Leadership, University of Virginia Allan R. Odden is Professor of Educational Leadership and Policy Analysis at University of Wisconsin-Madison, Director of Strategic Management of Human Capital, and Co-Director of the Consortium for Policy Research in Education in the Wisconsin Center for Education Research.